The new canadian agricultural policy. In search for a more prosperous, competitive, and innovative agricultural sector - Colomé, Rinaldo Antonio (2013)
Fil: Colomé, Rinaldo Antonio. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.